Elite-level coaches' coping: Stress appraisal and COVID-19 - Østerås, M. G. O.; Haugan, J. A.; Moen, F. (The Sport Journal, 2023)
The current study investigated 97 Norwegian elite-level coaches` appraisal of working as a coach during the COVID-19 pandemic, and the predictive outcomes of these cognitive processes. The participants were part of a Norwegian coach education program carried out by the Norwegian Olympic Sport Center (NOSC). The results in the current study show that the coaches appraised their work during the pandemic as controllable-by-self, as a challenge, as controllable-by-others, and stressful. The regression analysis showed that challenge and controllable-by-self were unique and positive significant predictors of the coaches` subjective performance, and that controllable-by-self was the strongest predictor of the two. Appraising the situation as uncontrollable-by-anyone was also a significant positive predictor of coaches` subjective performance in the step 2 of the regression analysis, and not coaches` exhaustion level as hypothesized. Threat appraisals were found to significant predict coaches` exhaustion level at the first step of the regression analysis, whereas controllable-by-self was the strongest negative significant predictor for coaches` exhaustion. The results indicate that controllable-by-self appraisals play a particular role in preventing burnout and inducing performance in elite coaches when they face stressors such as the COVID-19 pandemic.